2018
DOI: 10.1073/pnas.1806123115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of reticular gigantocellularis neurons indicates that eNOS modulates environmentally dependent levels of arousal

Abstract: Neurons of the medullary reticular nucleus gigantocellularis (NGC) and their targets have recently been a focus of research on mechanisms supporting generalized CNS arousal (GA) required for proper cognitive functions. Using the retro-TRAP method, we characterized transcripts enriched in NGC neurons which have projections to the thalamus. The unique expression and activation of the endothelial nitric oxide (eNOS) signaling pathway in these cells and their intimate connections with blood vessels indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 57 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…LC is reported to receive inputs from up to 111 distinct brain regions, including most brain-stem and forebrain regions ( Schwarz et al, 2015 ; Breton-Provencher and Sur, 2019 ; Figure 1B ). Brainstem inputs, most notably from the gigantocellular reticular nucleus ( Jones and Yang, 1985 ) – which responds to tactile, visual, vestibular, and olfactory stimuli ( Tabansky et al, 2018 ) – result in LC activation following salient sensory stimuli. Meanwhile, top-down inputs from the prefrontal cortex (PFC) and central amygdala can modulate the intensity of LC activation ( Sara and Hervé-Minvielle, 1995 ; Jodo et al, 1998 ; McCall et al, 2015 ).…”
Section: Anatomy Of the Ne Systemmentioning
confidence: 99%
“…LC is reported to receive inputs from up to 111 distinct brain regions, including most brain-stem and forebrain regions ( Schwarz et al, 2015 ; Breton-Provencher and Sur, 2019 ; Figure 1B ). Brainstem inputs, most notably from the gigantocellular reticular nucleus ( Jones and Yang, 1985 ) – which responds to tactile, visual, vestibular, and olfactory stimuli ( Tabansky et al, 2018 ) – result in LC activation following salient sensory stimuli. Meanwhile, top-down inputs from the prefrontal cortex (PFC) and central amygdala can modulate the intensity of LC activation ( Sara and Hervé-Minvielle, 1995 ; Jodo et al, 1998 ; McCall et al, 2015 ).…”
Section: Anatomy Of the Ne Systemmentioning
confidence: 99%
“…Consistent with our results, the restitution of BDNF/TrkB signaling after a stroke enhanced neuroprotection in the cerebral cortex 58 . Moreover, further recent studies have confirmed the functional implications of eNOS expression in neurons 59 . We focused on NF-κB, a known target of NO and also implicated in both neuroprotective and neurotoxic effects.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with our results, the restitution of BDNF/TrkB signaling after a stroke enhanced neuroprotection in the cerebral cortex 53 . Moreover, further recent studies have confirmed functional implications of eNOS expression in neurons 54 . We focused on NF-κB, a known target of NO and also implicated in both neuroprotective and neurotoxic effects.…”
Section: Discussionmentioning
confidence: 73%